Strategi Edukasi-Islam Kreatif di Instagram bagi Mahasiswa Gen Z FAD UPN Veteran Jawa Timur - Mohamad Arya Mizar; Muhammad Ifris Putra Laksono; Erina Irsyadiyah; Tiara Aulia Arsa; Nashwa Aqila Yudhiestira (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to investigate the effectiveness of creative-educational content on the Instagram platform to educate students of the Faculty of Architecture and Design (FAD) UPN Veteran East Java about Islamic teachings and values in the digitalization era. The research method used is qualitative and quantitative by distributing questionnaires and digging deeper into the content that can be trusted and in accordance with the teachings in Islam. With this research, it is hoped that it can provide more in-depth knowledge about effective strategies and redevelop existing strategies to be more varied and reach and involve generation Z, especially students of the Faculty of Architecture and Design.